Coenzyme Q10 or Creatine Counteract Pravastatin-Induced Liver Redox Changes in Hypercholesterolemic Mice - Marques, Ana C.; Busanello, Estela N. B.; de Oliveira, Diogo N.; Catharino, Rodrigo R.; Oliveira, Helena C. F.; Vercesi, Anibal E. (Frontiers in Pharmacology, 2018)
Statins are the preferred therapy to treat hypercholesterolemia. Their main action consists of inhibiting the cholesterol biosynthesis pathway. Previous studies report mitochondrial oxidative stress and membrane permeability transition (MPT) of several experimental models submitted to diverse statins treatments. The aim of the present study was to investigate whether chronic treatment with the hydrophilic pravastatin induces hepatotoxicity in LDL receptor knockout mice (LDLr-/-), a model for human familial hypercholesterolemia. We evaluated respiration and reactive oxygen production rates, cyclosporine-A sensitive mitochondrial calcium release, antioxidant enzyme activities in liver mitochondria or homogenates obtained from LDLr-/- mice treated with pravastatin for three months. We observed that pravastatin induced higher H2O2 production rate (40%), decreased activity of aconitase (28%), a superoxide-sensitive Krebs cycle enzyme, and increased susceptibility to Ca2+-induced MPT (32%) in liver mitochondria. Among several antioxidant enzymes, only glucose-6-phosphate dehydrogenase (G6PD) activity was increased (44%) in the liver of treated mice. Reduced glutathione content and reduced to oxidized glutathione ratio were increased in livers of pravastatin treated mice (1.5- and 2-fold, respectively). The presence of oxidized lipid species were detected in pravastatin group but protein oxidation markers (carbonyl and SH- groups) were not altered. Diet supplementation with the antioxidants CoQ10 or creatine fully reversed all pravastatin effects (reduced H2O2 generation, susceptibility to MPT and normalized aconitase and G6PD activity). Taken together, these results suggest that 1- pravastatin induces liver mitochondrial redox imbalance that may explain the hepatic side effects reported in a small number of patients, and 2- the co-treatment with safe antioxidants neutralize these side effects.